2019
DOI: 10.1128/jvi.01328-19
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the First Gene Transfer Agent (GTA) Small Terminase in Rhodobacter capsulatus and Its Role in GTA Production and Packaging of DNA

Abstract: Random transfer of any and all genes between bacteria could be influential in the spread of virulence or antimicrobial resistance genes. Discovery of the true prevalence of GTAs in sequenced genomes is hampered by their apparent similarity to bacteriophages. Our data allowed the prediction of small terminases in diverse GTA producer species, and defining the characteristics of a “GTA-type” terminase could be an important step toward novel GTA identification. Importantly, the GTA small terminase shares many fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…When particular functional genome modules in their respective order were focused on, the following differences were observed. A comparison of the amino acid sequences of the terminase small subunit (TerS), which tends to be one of the least conserved phage proteins (42), divides known S. epidermidis phietaviruses into two subgroups, where phages 27, 48, and E72 represent one and phages 456 and 459 represent the other (Fig. 5A).…”
Section: Resultsmentioning
confidence: 99%
“…When particular functional genome modules in their respective order were focused on, the following differences were observed. A comparison of the amino acid sequences of the terminase small subunit (TerS), which tends to be one of the least conserved phage proteins (42), divides known S. epidermidis phietaviruses into two subgroups, where phages 27, 48, and E72 represent one and phages 456 and 459 represent the other (Fig. 5A).…”
Section: Resultsmentioning
confidence: 99%
“…The RcGTA gene g1 , which is adjacent to the terL gene (g2) in the RcGTA genome, has been recently shown to encode TerS ( Sherlock, Leong, and Fogg 2019 ). Sherlock, Leong, and Fogg (2019) demonstrated that the RcGTA TerS binds non-specifically to DNA with low affinity due to the absence of a specific DNA-binding domain and the retention of non-specific DNA binding activity. A TerS protein with altered DNA-binding characteristics and a modified headful TerL might together underlie the random packaging that is characteristic of RcGTA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to TerL, other GTA proteins that are involved in DNA packaging, including TerS and portal, might contribute to the unique DNA packaging features of RcGTA. In particular, the RcGTA gene g1, which is adjacent to the terL gene (g2) in the RcGTA genome, has been recently shown to encode TerS (Sherlock et al, 2019). Sherlock et al (2019) demonstrated that the RcGTA TerS binds non-specifically to DNA with low affinity due to the absence of a specific DNA-binding domain and the retention of non-specific DNA binding activity.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the RcGTA gene g1, which is adjacent to the terL gene (g2) in the RcGTA genome, has been recently shown to encode TerS (Sherlock et al, 2019). Sherlock et al (2019) demonstrated that the RcGTA TerS binds non-specifically to DNA with low affinity due to the absence of a specific DNA-binding domain and the retention of non-specific DNA binding activity. A TerS protein with altered DNA-binding characteristics and a modified headful TerL might together underlie the random packaging that is characteristic of RcGTA.…”
Section: Discussionmentioning
confidence: 99%